A Novel Approach for In Vitro Testing and Hazard Evaluation of Nanoformulated RyR2-Targeting siRNA Drugs Using Human PBMCs - Valeria Bettinsoli; Gloria Melzi; Angelica Crea; Lorenzo Degli Esposti; Michele Iafisco; Daniele Catalucci; Paolo Ciana; Emanuela Corsini (Life)
Nucleic acid (NA)-based drugs are promising therapeutics agents. Beyond efficacy, addressing safety concerns—particularly those specific to this class of drugs—is crucial. Here, we propose an in vitro approach to screen for potential adverse off-target effects of NA-based drugs. Human peripheral blood mononuclear cells (PBMCs), purified from buffy coats of healthy donors, were used to investigate the ability of NA-drugs to trigger toxicity pathways and inappropriate immune stimulation. PBMCs were selected for their ability to represent potential human responses, given their likelihood of interacting with administered drugs. As proof of concept, a small interfering RNA (siRNA) targeting Ryanodine Receptor mRNA (RyR2) identified by the Italian National Center for Gene Therapy and Drugs based on RNA Technology as a potential therapeutic target for dominant catecholaminergic polymorphic ventricular tachycardia, was selected. This compound and its scramble were formulated within a calcium phosphate nanoparticle-based delivery system. Positive controls for four toxicity pathways were identified through literature review, each associated with a specific type of cellular stress: oxidative stress (tert-butyl hydroperoxide), mitochondrial stress (rotenone), endoplasmic reticulum stress (thapsigargin), and autophagy (rapamycin). These controls were used to define specific mRNA signatures triggered in PBMCs, which were subsequently used as indicators of off-target effects. To assess immune activation, the release of pro-inflammatory cytokines (interleukin-6, interleukin-8, tumor necrosis factor-α, and interferon-γ) was measured 24 h after exposure. The proposed approach provides a rapid and effective screening method for identifying potential unintended effects in a relevant human model, which also allows to address gender effects and variability in responses.